(untitled) (Journal of Electrical Engineering, 2012)
In this paper an experimental approach of depositing diamond like carbon (DLC) on metal substrates has been described. By electrolysis of 10% (by mass) camphoric solution in methanol, attempts were made to deposit DLC films on Copper (Cu) and Aluminum (Al) substrates at room temperature. Solution is prepared using camphor (C10H16O), a natural source in methanol solvent. At first we applied this approach on Cu substrate and then on Al substrate. The surface morphologies of deposited films were examined by scanning electron microscopy (SEM). A comparison between Cu and Al substrates has been also presented under this approach. Journal of Electrical Engineering The Institution of Engineers, Bangladesh Vol. EE 37, No. II, December, 2011